2022
DOI: 10.3390/antibiotics11060735
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan: A Small Molecule with Controversial Roles

Abstract: Triclosan (TCS), a broad-spectrum antimicrobial agent, has been widely used in personal care products, medical products, plastic cutting boards, and food storage containers. Colgate Total® toothpaste, containing 10 mM TCS, is effective in controlling biofilm formation and maintaining gingival health. Given its broad usage, TCS is present ubiquitously in the environment. Given its strong lipophilicity and accumulation ability in organisms, it is potentially harmful to biohealth. Several reports suggest the toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 247 publications
0
17
0
Order By: Relevance
“…In addition, the effective microbial spectrum of antimicrobial sutures has been reported to include all major bacterial species causing SSI in the orthopedic field. [ 24 , 25 ] Triclosan-coated sutures not only help to protect against bacterial colonization of the suture itself, but also create an area of growth inhibition around the suture, indicating that antimicrobial Vicryl® not only protects against wound infection, but also inhibits the growth of bacteria that have already penetrated and attached to the implant, thereby preventing further development of deep-seated infections.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effective microbial spectrum of antimicrobial sutures has been reported to include all major bacterial species causing SSI in the orthopedic field. [ 24 , 25 ] Triclosan-coated sutures not only help to protect against bacterial colonization of the suture itself, but also create an area of growth inhibition around the suture, indicating that antimicrobial Vicryl® not only protects against wound infection, but also inhibits the growth of bacteria that have already penetrated and attached to the implant, thereby preventing further development of deep-seated infections.…”
Section: Discussionmentioning
confidence: 99%
“…To remove pollutants that polymerize, the wastewater is then filtered or sedimented [243,245]. Sun et al (2019) proved that the way to remove triclosan, a compound with antibacterial properties, which is resistant to biodegradation [246][247][248], from water is the enzymatic activity of the T. versicolor laccase supported by Cu 2+ ions [137], in which mainly triclosan dimers, trimers and tetramers are produced. A possible transformation mechanism of the xenobiotic was proposed: (i) laccase catalyzes the oxidation of triclosan to produce intermediate phenoxy radicals, and (ii) phenoxy radicals link together via C-C and C-O-C radical covalent bonds, forming mainly oligomers.…”
Section: Mechanism Of Removing Xenobiotics From Watermentioning
confidence: 99%
“…Triclosan is a disinfectant found in PCPs, though it has now been banned in soap products in many countries (Sinicropi et al, 2022). One study evolving Stenotrophomonas maltophilia in the presence of triclosan found reduced susceptibility to tetracycline, chloramphenicol, and ciprofloxacin, mediated through overexpression of the multidrug efflux pump SmeDEF (Sanchez et al, 2005).…”
Section: Co-selectionmentioning
confidence: 99%